Impact of Cypermethrin on Fingerlings of Common Edible Carp (Labeo rohita). (30th April 2012) - Tiwari, Sudhanshu; Tiwari, Richa; Singh, Ajay
Abstract : Laboratory evaluations were made to assess the toxicological and biochemical effect of cypermethrin on fingerlings of common edible freshwater culture carp (Labeo rohita) . There was a significant negative (P < 0.05 ) correlation observed between effective doses of cypermethrin and exposure periods; that is, LC50 values decreased from 0.323 μg/L (6 h) to > 0.278 μg/L (12 h), > 0.240 μg/L (18 h) and >0.205 μg/L (24 h). Exposure to sublethal doses of cypermethrin for 24 h and 96 h exposure period caused significant (P < 0.05 ) time- and dose-dependent alterations in total protein, total free amino acids, nucleic acids, glycogen, pyruvate, and lactate level and in the activity of enzyme protease, alanine aminotransferase, aspartate aminotransferase, acid phosphatases, alkaline phosphatases, acetylcholinesterase, and cytochrome oxidase in liver and muscle tissues of fish. Thus, cypermethrin has potent piscicidal activity against fingerlings of fish Labeo rohita and adversely affects their behavioural patterns, shifting aerobic pathway of fish respiration towards anaerobic pathway and also inhibiting energy production by suppressing ATP synthesis.